2002
DOI: 10.1081/amp-120014241
|View full text |Cite
|
Sign up to set email alerts
|

TRIBOLOGICAL EVALUATION OF ULTRAFINE Ti(CN) CERMETS

Abstract: High temperature wear performance of ultrafine and coarse grade Ti(CN)-WC -Ni cermets was investigated by surface profilometry, atomic force microscopy, and scanning electron microscopy to ascertain the contribution of particle size effect. The observed wear depths, produced during wear test, showed direct correlation with the surface roughness, which in turn is controlled by the microstructural features. The cermets with ultrafine Ti(CN) exhibit greater homogeneity along with a considerably higher rim fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Titanium carbonitrides based cermet's are considered as candidate materials for machining purposes in the tool industry, because they possess high mechanical properties and high wear performance [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Titanium carbonitrides based cermet's are considered as candidate materials for machining purposes in the tool industry, because they possess high mechanical properties and high wear performance [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The cores are the undissolved Ti(CN) while the rim comprises of solid solution of Ti(CN), secondary carbides and binder. Recent studies on sintered Ti(C 0.5 N 0.5 )-WC-Ni cermets have shown that the incorporation of ultrafine Ti(C 0.5 N 0.5 ) particles to the pre-sintered powder mix enhances the tribo-mechanical properties over coarse grade cermets [8][9][10]. This was attributed to a much better distribution of hard phases in the microstructure of as-sintered ultrafine cermet, apart from an improved lattice coherency.…”
Section: Introductionmentioning
confidence: 99%
“…The latter requires accurate measurement of the magnetic induction and this can be achieved with a 3D form of electron holography [22]. Indeed, three-dimensional analysis will also become increasingly important not only for functional materials but also for nanoscale structural and engineering materials, such as ultra-fine cermets [23]. In the catalysis industry, heterogeneous catalysts [24] are now designed with nanometre-sized active particles distributed in three dimensions on or within a porous support structure-the tomography of such catalysts will be discussed later in the chapter.…”
Section: Introductionmentioning
confidence: 99%